Impact of Vegetation Cover Changes on Soil Erosion in Typical Forest Stands in South China - WANG Juan; HUANG Tingting; ZHAO Hui; LIU Xiaolin; JIN Pingwei; SHI Yandong (Renmin Zhujiang)
This study aims to analyze the relationship between changes in vegetation cover resulting from burning, clear-cutting, and thinning in forest stands, and soil erosion. By clarifying how different regeneration methods affect vegetation cover and its subsequent impact on soil erosion, this research aims to provide crucial data support. Through remote sensing monitoring and field investigations, this study quantitatively evaluates the differences in vegetation cover changes and their impact on soil erosion in forested areas. The changes in fractional vegetation cover (FVC) indicated that the vegetation cover at sampling points WH1 and WH2 in Wuhua County decreased from 0.5 to below 0.3 after burning. Similarly, the vegetation cover at sampling points CT1 to CT3 in Changting County decreased to below 0.4 after clear-cutting. Soil erosion impacts were mainly observed from April to August. For instance, after the burning of the sites, the monthly average soil erosion modulus at WHI decreased by 8% to 65%, while at WH2, it increased by 8% to 101%. In clear-cut areas, the monthly average soil erosion modulus at CT1 and CT2 ranged from 3 to 16 times that of the same period in 2020. Thinning resulted in monthly average soil erosion modulus at CT3 being 1 to 6 times that of the same period in 2020. The correlation coefficients between vegetation cover and soil erosion modulus changes after burning, clear-cutting, and thinning were 0.63, 0.87, and 0.52, respectively. Clear-cutting had a more pronounced effect on increasing soil erosion modulus compared to burning and thinning, especially in the short term. The findings contribute valuable insights into the understanding of soil erosion dynamics in forest ecosystems, thus informing better soil and water conservation practices.